2014
DOI: 10.3732/ajb.1300435
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic control of osmolality and ionic composition of the xylem sap in two mangrove species

Abstract: • Premise of the study: Xylem sap osmolality and salinity is a critical unresolved issue in plant function with impacts on transport efficiency, pressure gradients, and living cell turgor pressure, especially for halophytes such as mangrove trees.• Methods: We collected successive xylem vessel sap samples from stems and shoots of Avicennia germinans and Laguncularia racemosa using vacuum and pressure extraction and measured their osmolality. Following a series of extractions with the pressure chamber, we depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…From three of six branches, side twigs were removed, and the remaining main axes (main stem length, 50-60 cm; side stem length, less than 20 cm) were completely debarked, washed with distilled water, and dried with paper towels. Branches were debarked to avoid reverse osmosis from living cells during xylem sap extraction (López-Portillo et al, 2014). Furthermore, this procedure should prevent the contamination of extracted sap with resin.…”
Section: Seasonal Coursementioning
confidence: 99%
“…From three of six branches, side twigs were removed, and the remaining main axes (main stem length, 50-60 cm; side stem length, less than 20 cm) were completely debarked, washed with distilled water, and dried with paper towels. Branches were debarked to avoid reverse osmosis from living cells during xylem sap extraction (López-Portillo et al, 2014). Furthermore, this procedure should prevent the contamination of extracted sap with resin.…”
Section: Seasonal Coursementioning
confidence: 99%
“…First, mangrove tree species growing under increasingly saline environments can have greater xylem vessel grouping and vessel density, as well as reduced vessel diameters and lengths than their low-salinity conspecifics, which is proposed to reduce the risk of embolisms associated with highly negative water potentials 45 . Second, some mangroves – those that secrete salt from their leaf and bark surfaces – can dynamically control xylem ion composition 46 to increase hydraulic conductivity 47 as water potential becomes more negative, whilst maintaining relatively stable stomatal conductance (and transpiration). This dynamic xylem sap osmolality control increases the water available to the transpiration stream without actively increasing transpiration, further reducing the risk of embolisms under salt stress 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Second, some mangroves – those that secrete salt from their leaf and bark surfaces – can dynamically control xylem ion composition 46 to increase hydraulic conductivity 47 as water potential becomes more negative, whilst maintaining relatively stable stomatal conductance (and transpiration). This dynamic xylem sap osmolality control increases the water available to the transpiration stream without actively increasing transpiration, further reducing the risk of embolisms under salt stress 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Osmotic adjustments are necessary for mangroves to resist substrate salinity and to maintain constant turgor pressure (Méndez-Alonzo et al 2016). López-Portillo et al (2014) reported that xylem sap osmolality and ionic contents affect turgor pressure, hydraulic conductivity, and water potential. Hydraulic properties can be interrupted by a break in xylem vessels.…”
Section: Salinitymentioning
confidence: 99%